STRATEGI PENGEMBANGAN JAMBU GONDANG MANIS JOMBANG - Triya Titin Aisiyaturrochiyah; Miftachul Chusnah (Program Studi Agribisnis, 2021)
This study aims to identify what internal and external factors can be strengths, weaknesses, opportunities and threats to the Gondang Sweet Guava development strategy in the Gondang Manis Farmer Group. Gondang Sweet Village, Perak District, Jombang Regency. This study uses the SWOT analysis method obtained from the IFAS/EFAS matrix, SWOT quadrant and SWOT matrix. The respondents of this study were the Head of the Banjarsari Farmers Group and 15 members who were members of the Gondang Manis farmer group. Based on the results of the analysis of the IFAS matrix, the total score is 2.48, the results of the EFAS matrix analysis the total score is 2.51. After knowing the results of the IFAS/EFAS matrix, then determining the SWOT quadrant. Quadrant results show the Gondang Manis farmer group is in quadrant 1 (Grouth), namely the Gondang Manis farmer group in developing Guava needs a strategy to create new strategies to deal with various kinds of threats. The main strategy is to improve the quality of guava by harvesting it properly and properly. And produce other strategies including the strategy of improving the quality of guava through coaching pokdarwis and youth groups, maintaining the quality of guava gondang sweet. increase people's purchasing power, reduce competition between guava farmers.